The role of 2D/3D spin-polarization interactions in hybrid copper hydroxide acetate: new insights from first-principles molecular dynamics - Chaker, Ziyad; Ori, Guido; Boero, Mauro; Massobrio, Carlo (Beilstein Journal of Nanotechnology, 2017)
The magnetic properties response of the layered hybrid material copper hydroxide acetate Cu2(OH)3CH3COO·H2O is studied as a function of the applied pressure within first-principles molecular dynamics. We are able to elucidate the interplay between the structural properties of this material and its magnetic character, both at the local (atomic) level and at the bulk level. We performed a detailed analysis of the intralayer spin configurations occurring for each value of the imposed projection along the z-axis for the total spin and of the applied pressure. The transition from an antiferromagnetic to a ferromagnetic state at high pressure (above 3 GPa) goes along with a vanishing difference between the spin polarizations pertaining to each layer. Therefore, at high pressure, copper hydroxide acetate is a ferromagnet with no changes of spin polarization in the direction perpendicular to the inorganic layers.
Keywords: first-principles molecular dynamics; hybrid material; magnetic properties; pressure; spin polarization